Pengaruh Model Pembelajaran Problem Based Learning (PBL) Pada Materi Matriks Terhadap Hasil Belajar Matematika Peserta Didik Kelas XI SMK Ma’arif Husnul Khatimah - Ishak, suryadi (Sigma: Jurnal Pembelajaran dan Pendidikan Matematika Sawerigading, 2024)
This experimental study aims to determine the effectiveness of the use of the Problem Based Learning (PBL) model on the topic of matrices in relation to the mathematics learning outcomes of eleventh-grade students at SMK Ma'arif Husnul Khatimah. The total number of participants was 88 students, with the sample consisting of 15 students from the Multimedia class and 15 students from the Fashion Design class. The research instruments included tests on student learning outcomes, student activity sheets, the implementation of learning, and student response questionnaires. The collected data were analyzed using descriptive and inferential statistical analysis. From the statistical analysis, the average pretest score in the experimental class was 52.00, while in the control class it was 52.66. The average posttest score in the experimental class was 83.85, while in the control class it was 70.66. In terms of student activity, the average percentage was 88.05%. For the student response, the average percentage was 98.99%. The results of the t-test calculation for the posttest data showed a t-value of 3.265, while the t-table value was 2.656, meaning that t_calculated > t_table, or 3.265 > 2.656. From the results of the descriptive and inferential statistical analysis, it is concluded that the use of the Problem Based Learning (PBL) model on the topic of matrices has a significant effect on the mathematics learning outcomes of eleventh-grade students at SMK Ma'arif Husnul Khatimah.